1995
DOI: 10.1080/0924345950060204
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Educational Practice through Performance Indicators

Abstract: School effectiveness research has provided us with the knowledge and techniques to produce fair performance indicators. But under what circumstances do performance indicators have the most influence? For ten years the A Level Information System (ALIS) has been feeding back quantitative summaries of educational performance to schools, department by department, in an effort to improve educational provision. During that time the feedback has regularly been accompanied by dissemination meetings at which the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Of most relevance to the current discussion, however, would be studies of the impact of performance feedback conducted in school contexts. Such studies include those by Fuchs and Fuchs (1986), Cohen (1980), L"Hommedieu et al, (1988,1990), Edelenbos (1992, 1998), Tymms (1995Tymms ( , 1997aTymms ( , 1997b and Coe (1998b). All these studies have been reviewed in more detail by Coe (2002).…”
Section: Specific Application To School Performance Feedbackmentioning
confidence: 99%
“…Of most relevance to the current discussion, however, would be studies of the impact of performance feedback conducted in school contexts. Such studies include those by Fuchs and Fuchs (1986), Cohen (1980), L"Hommedieu et al, (1988,1990), Edelenbos (1992, 1998), Tymms (1995Tymms ( , 1997aTymms ( , 1997b and Coe (1998b). All these studies have been reviewed in more detail by Coe (2002).…”
Section: Specific Application To School Performance Feedbackmentioning
confidence: 99%
“…It is clear, however, that the current system of National Targets is not the only possible form of target setting in education policy. There are four main criteria for effective educational targets (Williamson et al, 1992;Nuttal, 1994;Tymms, 1995;Donald & Denison, 1996;Loveman, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Targets must be accepted and valued by those expected to achieve them if they are to succeed. Research into the use of performance indicators in A level provision has highlighted the need for such measures to be seen by practitioners as 'tools for the professional', to inform future provision rather than external, punitive means of public accountability, if they are to be accepted (Tymms, 1995). As Williamson et al (1992, p. 186) conclude, 'empowerment rather than prescription must be the way forward'.…”
Section: Discussionmentioning
confidence: 99%
“…Many projects in this field have also demonstrated that providing school-focused training courses can help establish this precondition. For example, Tymms notes how inviting teachers to attend an inservice workshop about handling student performance data gave rise to more positive attitudes towards one such system (ALIS, A-level information system : Tymms 1995;1997). Demie (2003) also notes how successful an inner-city local education authority's school-focused training courses were for head teachers and senior management teams in schools.…”
Section: U Maiermentioning
confidence: 99%